A Proposed Implementation of Integrated Good Corporate Governance Assessment in Sub Holding Commercial & Trading Pertamina - Tabri, Muhamad Alis; Putro, Utomo Sarjono (Integrasi Sains Media, 2025)
Good Corporate Governance (GCG) is an essential foundation for companies, particularly State-Owned Enterprises (SOEs), to ensure transparency, accountability, and sustainable business growth. Within Pertamina’s Sub-Holding Commercial & Trading, the current GCG assessment practices are conducted independently by each subsidiary, using varying methods, parameters, and assessors. This fragmented approach results in non-comparable outcomes and undermines the effectiveness of governance evaluation at the group level. To address this issue, this study proposes an integrated GCG assessment model that can be implemented uniformly across all entities within the Sub-Holding. The model is designed to support the Integrated Governance Committee (IGC), which functions as a risk management body under the Board of Commissioners, enabling it to evaluate governance implementation more effectively. Using a qualitative research methodology, data were collected through in-depth interviews with key internal stakeholders and complemented by secondary data from internal documents and relevant literature. The study applies theories of Business Process Reengineering (BPR) and Business Process Integration to develop a standardized assessment model. Key findings include the identification of inefficiencies in the current assessment system and the development of a centralized mechanism for determining assessment methods, selecting assessors, and executing evaluations. The study also outlines the necessary enablers, including policy development, resource allocation, and unified assessment parameters. The proposed integrated model enhances data comparability, improves coordination, and ensures consistency in evaluating GCG implementation across the group. This approach contributes to strengthening governance practices within SOEs and serves as a reference for similar organizational structures.